The LINCE Project: A Pathway for Diagnosing NCL2 Disease - Rodrigues, Daniel; de Castro, Maria José; Crujeiras, Pablo; Duat-Rodriguez, Anna; Marco, Ana Victoria; del Toro, Mireia; Couce, María L.; Colón, Cristóbal (Frontiers in Pediatrics, 2022)
Introduction: Neuronal Ceroid Lipofuscinosis (NCL) comprises a clinically and genetically heterogeneous group of 13 neurodegenerative lysosomal storage disorders. Neuronal Ceroid lipofuscinosis type 2 disease (NCL2), caused by the deficient lysosomal enzyme tripeptidyl peptidase 1 (TPP1), is the only one with an approved enzyme replacement treatment (ERT). Early initiation of ERT appears to modify significantly the natural history of the disease. We aimed to shorten the time to diagnosis of NCL2. Methods: In March 2017, we started per first time in Spain a selective screening program, the LINCE project, in pediatric patients with clinical symptoms compatible with NCL2 disease. The program covered the whole country. We distributed kits to pediatricians with the necessary material to assess patients. All samples in this study were received within one week of collection. Enzymatic activity determined on dried blood spots was the main method used to screen for TPP1 and palmitoyl protein thioesterase 1 (PPT1) for the differential diagnosis with neuronal ceroid lipofuscinosis type 1 (NCL1). Results: Over a period of three years, we received 71 samples. The analysis was minimally invasive, relatively cheap and fast-executing. Three cases identified as a direct result of the selective screening strategy were confirmed by genetic study of NCL2 disease with a median age of 4.5 years. Our screening method has a specificity of 100%, and, with the absence to date of false negatives. We did not detect any NCL1-positive cases. Conclusions. LINCE proved to be a simple, useful, and reliable tool for the diagnosis of NCL2, enabling clinicians to diagnose NCL2 faster. The presence of NCL2-positive cases in our population and availability of treatment may facilitate the inclusion of NCL2 in neonatal screening programs for early diagnosis.